Implementation of Home Visit Program in an Effort to Improve the Nutritional Status of Toddlers in Developing Countries: Scoping Review - Siti Zakiah Zulfa (EMBRIO: Jurnal Kebidanan, 2024)
Malnutrition in toddlers is still a severe problem in developing countries. This study aims to determine how the home visit program is implemented in an effort to improve the nutritional status of toddlers in developing countries. This study used the scoping review framework from Arksey and O'Malley (2005). The articles chosen are published from 2010 to 2019 in developing countries. The article was obtained from the PubMed, Wiley, EBSCO, ScienceDirect, and Google Scholar databases. Article selection process using the Mendeley and Covidence applications. Five of the 159 articles selected showed that a combined home visiting program could rehabilitate underweight 5x faster (OR equal 4.74, 95percent CI equal 2.47-9.09), significantly reduce moderate malnutrition (-3.3 vs. -1.5; p less than 0, 0001) and severe malnutrition (-3.8 vs. -1.8; p less than 0.001) and 55percent of children achieved recovery z-score more than equal -1 which took an average of 14 weeks. Additionally, wasting was reduced by 27 percent (aOR: 0.73, 95 percent CI: 0.55–0.97), underweight by 40 percent (aOR: 0.60, 95 percent CI: 0.47–0.75), and stunting by 27 percent (aOR: 0.73, 95 percent CI: 0.57–0.93). This study concludes that the home visit program is an effective and significant strategy to reduce the incidence of underweight, moderate and severe malnutrition, stunting, and wasting in toddlers only when combined with other programs. Several research gaps were also identified, which could be confirmed through further research.